2021
DOI: 10.1051/sicotj/2021022
|View full text |Cite
|
Sign up to set email alerts
|

Posterior shoulder dislocation with reverse Hill-Sachs lesion. A technical note and report of two cases

Abstract: Posterior shoulder dislocation (PSD) with a reverse Hill-Sachs lesion is a rare injury with challenging management. This article is a technical note, describing the combination of both, modified McLaughlin procedure with posterior Bankart repair, for the surgical treatment of traumatic PSD associated with a substantial reverse Hill-Sachs lesion. Two patients with mid-term follow-up are presented. Approaching and repairing both sides of the joint, balance and congruency are restored, the humeral head is central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 11 - 16 ] In addition, the literature review revealed that a significant number of neglected (late presenting or overlooked) patients, particularly those with reverse Hill-Sachs lesions between 20 and 45%, were treated with the modified McLaughlin procedure. [ 1 , 6 , 28 - 34 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 11 - 16 ] In addition, the literature review revealed that a significant number of neglected (late presenting or overlooked) patients, particularly those with reverse Hill-Sachs lesions between 20 and 45%, were treated with the modified McLaughlin procedure. [ 1 , 6 , 28 - 34 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] In addition, the literature review revealed that a significant number of neglected (late presenting or overlooked) patients, particularly those with reverse Hill-Sachs lesions between 20 and 45%, were treated with the modified McLaughlin procedure. [1,6,[28][29][30][31][32][33][34]37] Khira and Salama [28] reported the results (n=12) of an open reduction and reconstruction of the humeral head defect using the McLaughlin technique modified by Hawkins et al, [10] in which the insertion of the subscapularis muscle was displaced with lesser tuberosity and augmented with a bone graft from the iliac crest fixed with screws. In their study, the time between dislocation and diagnosis ranged from four weeks to three months, with a mean of eight weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation